PENINGKATAN KOMPETENSI PROFESIONAL GURU AGAMA MELALUI PEMBINAAN SUPERVISI PENDIDIKAN DI SMP NEGERI 1 LAWE ALAS KECAMATAN LAWE ALAS KABUPATEN ACEH TENGGARA - Pinim, Juherman (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2020)
In accordance with the conditions at SMP Negeri 1 Lawe, Aceh Tenggara District, it shows that teachers have professional competence, this is indicated by the ability of teachers to master material in teaching broadly and deeply, teach according to the curriculum, be able to relate subject matter to others, and are able to apply in everyday life. The existence of this professional competence is inseparable from the supervision coaching carried out for teachers, but to be clearer about increasing the professional competence of teachers through supervision guidance, a deeper study will be carried out through research. Based on the aforementioned background, it becomes the rationale for the author so that he sets the title: Increasing the Professional Competence of Islamic Religion Teachers through Education Supervision Development at SMP Negeri 1 Lawe Alas, Southeast Aceh Regency. The problem in this study is how to increase the professional competence of Islamic religious teachers at SMP Negeri 1 Lawe Alas, Southeast Aceh Regency. How is the supervision of Islamic religious teacher education at SMP Negeri 1 Lawe Alas, Southeast Aceh Regency through supervision guidance. What are the obstacles that have been experienced in increasing the prefunctional competence of Islamic religious teachers at SMP Negeri 1 Lawe Alas, Southeast Aceh Regency. This study is a qualitative study using interview data collection techniques for school principal informants, Islamic religious teachers. As for the results of this study, there is an increase in the professional competence of Islamic religious teachers at SMP Negeri 1 Lawe Alas, Lawe Alas District, Southeast Aceh Regency, this is marked by a broad and deep mastery of material which includes curriculum development, making syllabus and lesson plans, advancing learning methods, ability utilize technology, use concepts and learning units. There is an increase in the professional competence of Islamic religious teachers due to supervision guidance. Educational supervision is carried out through class visits, individual talks with the principal, group discussions, teaching demonstrations, class visits between teachers, curriculum development, attending workshops and conducting field research. The obstacles experienced in increasing teacher competence through educational supervision are the issue of implementation time which is sometimes inappropriate and the budget needed, especially in conducting field research as a requirement for teacher certification as an increase in teacher professional competence.